Beyond the Grind: The Intercultural Challenges and Cohesion Efforts in MiLB - Malcomb, Claire Sandman; Zitek, Emily M.; Grossman, Samuel; Parris, Benjamin (Frontiers in Psychology, 2025)
Minor League Baseball (MiLB) comprises players with a wide variety of backgrounds, including many born in the United States and Latin America, and these players spend years trying to work their way up to the Major League level. This paper describes a qualitative study that explores people’s experiences in MiLB, focusing on the challenges that players face and how these challenges might differ for players of different backgrounds. We interviewed 18 MiLB players, nine coaches, and two team education coordinators. Using a thematic analysis technique, we learned that the language barrier seemed to produce problems for the young players, especially those who spoke only Spanish and could not fully benefit from the coaching. Also, some interviewees talked to us about the challenges of intergroup relations, where cliques can form and some players may face biases from coaches. These results suggest that MiLB is challenging for everyone, but there are unique challenges for international Latino players and other minorities. However, we also learned that many teams are trying to solve these issues by offering language classes and other programs. Notably, many interviewees reported positive attitudes toward diversity. Ultimately, we found that while all players experience the same grind trying to make it to the Big Leagues, some players also experience unique and additional barriers to succeeding. We contribute to the broader conversation on the role of cultural diversity in sports.